2016
DOI: 10.1007/s11207-016-0926-x
|View full text |Cite
|
Sign up to set email alerts
|

Properties of Magnetic Tongues over a Solar Cycle

Abstract: The photospheric spatial distribution of the main magnetic polarities of bipolar active regions (ARs) presents during their emergence deformations are known as magnetic tongues. They are attributed to the presence of twist in the toroidal magnetic flux-tubes that form the ARs. The aim of this article is to study the twist of newly emerged ARs from the evolution of magnetic tongues observed in photospheric line-of-sight magnetograms. We apply the procedure described by Poisson et al. (2015, Solar Phys. 290, 727… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 23 publications
2
28
0
Order By: Relevance
“…In Sect. 3, we tested CoFFE using an analytical model based on the kinematic rise of a half-torus FR (see Poisson et al 2016). Using this model we are able to study the evolution of the axial and the azimuthal fields separately and to compare them with the core and tongue locations provided by CoFFE.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Sect. 3, we tested CoFFE using an analytical model based on the kinematic rise of a half-torus FR (see Poisson et al 2016). Using this model we are able to study the evolution of the axial and the azimuthal fields separately and to compare them with the core and tongue locations provided by CoFFE.…”
Section: Discussionmentioning
confidence: 99%
“…to minimise the contribution of the background magnetic flux (Poisson et al 2016). Movies for each AR were made to verify that the variable size box included all the magnetic flux of the AR at all times.…”
Section: Data Usedmentioning
confidence: 99%
“… 2011 ; Takizawa and Kitai 2015 ; Poisson et al. 2015 , 2016 ). Multiple observational studies showed that such yin-yang tongues are seen in flaring ARs, along with other observational characteristics including sigmoids, sheared coronal loops, and J-shaped flare ribbons (Li et al.…”
Section: Long-term and Large-scale Evolution: Observational Aspectsmentioning
confidence: 99%
“…The orientation of its magnetic fields is mostly West to East, although the presence of magnetic tongues leads to some deviation of the PIL orientation from that direction (Figure 1(c)). Following Poisson et al (2016), these tongues are interpreted as the contribution of the azimuthal field component of the emerging flux tube. They indicate a negative magnetic helicity, which is also suggested by the shear of the loops seen in the corona ( Figure 1(d)).…”
Section: Splitting Of the Eastern Filament Sectionmentioning
confidence: 99%